2021
DOI: 10.1111/iwj.13681
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the different progressions of early pressure injury by ultraviolet photography in rat models

Abstract: Early pressure injury (PI) can result in either spontaneous healing (SH) or deterioration into ulcer (DU). However, determining whether PI will progress into SH or DU on the basis of non-blanchable erythema only is difficult. In this study, we constructed two animal PI models to mimic SH and DU injuries and observed haemorrhage by using ultraviolet (UV) photography to develop potential clinical indicators for predicting the progression of early PI. Macroscopy, UV photography, and skin temperature observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…For example, the degree of erythema in early PI was rather lighter than in BE [ 8 ]. Our previous study found that this may be attributable to the fact that the erythema in early PI is a mixed lesion of multiple circulatory disturbances (e.g., hyperemia, congestion, and hemorrhage) [ 15 ]. Therefore, the erythema becomes more severe than the simple congestion of BE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the degree of erythema in early PI was rather lighter than in BE [ 8 ]. Our previous study found that this may be attributable to the fact that the erythema in early PI is a mixed lesion of multiple circulatory disturbances (e.g., hyperemia, congestion, and hemorrhage) [ 15 ]. Therefore, the erythema becomes more severe than the simple congestion of BE.…”
Section: Discussionmentioning
confidence: 99%
“…The CRTT was implemented using the transparent disc method. According to the method of a previous study [ 15 ], the pressure applied in the CRTT in the current study was set at 150 mmHg.…”
Section: Methodsmentioning
confidence: 99%
“…The PI rat model was adopted using magnetic compression focusing on I/R injury for the formation of skin ulcerations [ 66 , 67 ]. PI rat models were developed as described in a previous study [ 68 ]. The dorsal skin was gently pulled up and placed between 2 round magnetic disks measuring 10 mm and 3 mm in diameter and thickness respectively, with an average of 3000 Gauss magnetic force (NE05, Niroku Seisakusho Co., Ltd., Kobe, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…A simple prototype has been fabricated in a previous study where the UV brightness could be adjusted; however, the prototype lacked features such as pressure feedback, real-time monitoring, and a camera function. (16) In this study, we have designed a new portable monitoring device, which can quantitatively record the pressure from the diascope, precisely adjust the brightness of UV light and white light, and most importantly observe the patient's skin surface in real time and take high-quality photos for analysis. Figure 1 shows the portable skin-injury monitoring device and the major components within the measurement unit.…”
Section: Working Principle and Device System Configurationmentioning
confidence: 99%